2022
DOI: 10.1038/s41467-022-30606-y
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Anopheles mosquitoes expressing human PAI-1 impair malaria transmission

Abstract: In mammals, the serine protease plasmin degrades extracellular proteins during blood clot removal, tissue remodeling, and cell migration. The zymogen plasminogen is activated into plasmin by two serine proteases: tissue-type plasminogen activator (tPA) and urokinase-type plasminogen activator (uPA), a process regulated by plasminogen activator inhibitor 1 (PAI-1), a serine protease inhibitor that specifically inhibits tPA and uPA. Plasmodium gametes and sporozoites use tPA and uPA to activate plasminogen and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…That expression of antimalaria effectors in the salivary glands inhibited oocyst development in the midgut (Sg/E; Figure 3A ) is most likely explained by the fact that mosquitoes ingest saliva with the blood meal, in this way incorporating effector proteins into the blood bolus ( Luo et al, 2000 ). A similar phenomenon was also observed in a recent report showing that human PAI-1 expressed in salivary glands was ingested together with the saliva and inhibited oocyst formation ( Pascini et al, 2022 ). In our study, we confirmed the presence of the multi-effector protein, in addition to the AAPP salivary gland protein (control), in the midguts of Sg/E mosquitoes that express the multi-effector protein only in the salivary glands ( Appendix 1—figure 7 ).…”
Section: Discussionsupporting
confidence: 86%
“…That expression of antimalaria effectors in the salivary glands inhibited oocyst development in the midgut (Sg/E; Figure 3A ) is most likely explained by the fact that mosquitoes ingest saliva with the blood meal, in this way incorporating effector proteins into the blood bolus ( Luo et al, 2000 ). A similar phenomenon was also observed in a recent report showing that human PAI-1 expressed in salivary glands was ingested together with the saliva and inhibited oocyst formation ( Pascini et al, 2022 ). In our study, we confirmed the presence of the multi-effector protein, in addition to the AAPP salivary gland protein (control), in the midguts of Sg/E mosquitoes that express the multi-effector protein only in the salivary glands ( Appendix 1—figure 7 ).…”
Section: Discussionsupporting
confidence: 86%
“…(the latter two not under physiological conditions). [28][29][30][31] SERPINs of fibrinolysis are plasminogen activator inhibitors 1 and 2 (PAI-1/2) and α 2 -antiplasmin, whereas PAI-2 is predominantly intracellular, and its role in the regulation of fibrinolysis is controversial. [32][33][34][35] In order to study and monitor coagulation-related proteases, their respective substrates and specificities need to be explored.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Fibrinolysis is the process of fibrin clot degradation by plasmin [27] . Activation of plasminogen into plasmin can occur by various activators: tPA, urokinase‐type Plasminogen Activator (uPA, mainly extravascular), bacterial activators, FXIIa, and kallikrein from blood plasma (the latter two not under physiological conditions) [28–31] . SERPINs of fibrinolysis are plasminogen activator inhibitors 1 and 2 (PAI‐1/2) and α 2 ‐antiplasmin, whereas PAI‐2 is predominantly intracellular, and its role in the regulation of fibrinolysis is controversial [32–35] …”
Section: Introductionmentioning
confidence: 99%
“…A recent example of mosquito transgenesis using mosquitoes refractory to Plasmodium by expressing a mosquito restriction factor, has been published by Pascini et al (2022). Following the infectious blood meal, Plasmodium parasites bind plasminogen to their surface in the mosquito midgut lumen.…”
Section: Transgenic Approachesmentioning
confidence: 99%